Two new species of the Southeast Asian Dwarf tarantula genus Phlogiellus Pocock, 1887 (Theraphosidae, Selenocosmiinae) and a discussion on the taxonomic problem of the genus - Sivayyapram, Varat; Kunsete, Chawakorn; Songsangchote, Chaowalit; Thanoosing, Chawatat; Traiyasut, Prapun; Warrit, Natapot (Zootaxa, 2020)
Phlogiellus is one of the least studied theraphosid genera; there is only one recent revision on the genus. However, the “revision” only provided several taxonomic problems in the genus by giving unclear diagnostic characters of the genus and its species, using third party information in their descriptions and many of their examined specimens of are inaccessible. Here, we discuss the taxonomic problems of the genus, and provide a new genus description and diagnostic characters of Phlogiellus by combining information from previous studies with our examinations. Variation within species of previously diagnostic characters renders them of little value. In addition, two new Phlogiellus species from Myanmar and the Philippines are described and diagnosed here.